Pengembangan Media Pembelajaran Komik Berbasis Kemampuan Pemecahan Masalah Matematis - Ria Deswita; Ines Feltia Milenia; Selvia Erita (Journal on Education, 2022)
This study discusses the development of media in the form of comics based on mathematical problem solving abilities for grade VIII students of junior high school. One of the most important skills that students must master is the ability to solve mathematical problems. As a result, media is needed to help students better understand subject matter and improve their ability to solve mathematical problems. This study aims to develop comic media in learning mathematics based on the ability of junior high school students to solve mathematical problems. This research includes development research. This study uses the ADDIE methodology (Analysis, Design, Development, Implementation, and Evaluation). This research was conducted to determine the validity and practicality of comic media on the mathematical problem solving abilities of junior high school students. Based on the validation results to experts, the validity of comic learning media was 89.4% in the material aspect and 91.8% in the media aspect. Based on the test results, it was found that the practicality of comic learning media was 85.4% in the very practical category based on the results of the teacher's response questionnaire and 86.6% in the very practical category based on the results of the student response questionnaire. Thus, it was concluded that comic media in mathematics learning based on students' mathematical problem solving abilities is valid and practical to use in learning.